2023
DOI: 10.1038/s41598-023-34725-4
|View full text |Cite
|
Sign up to set email alerts
|

Early radial positional information in the cochlea is optimized by a precise linear BMP gradient and enhanced by SOX2

Abstract: Positional information encoded in signaling molecules is essential for early patterning in the prosensory domain of the developing cochlea. The sensory epithelium, the organ of Corti, contains an exquisite repeating pattern of hair cells and supporting cells. This requires precision in the morphogen signals that set the initial radial compartment boundaries, but this has not been investigated. To measure gradient formation and morphogenetic precision in developing cochlea, we developed a quantitative image ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…Previous studies quantitatively showed that the SOX2 domain that was once located on the medial edge on E12.5 was gradually repositioned to the center of the cochlear duct floor by E14.5 (Thompson et al, 2023). It is during this stage a prominent pool of progenitors are established in the IS domain where PORCN expression is enriched and adjacent to the SOX2positive cells in the sensory domain (Oliver et al, 2021).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Previous studies quantitatively showed that the SOX2 domain that was once located on the medial edge on E12.5 was gradually repositioned to the center of the cochlear duct floor by E14.5 (Thompson et al, 2023). It is during this stage a prominent pool of progenitors are established in the IS domain where PORCN expression is enriched and adjacent to the SOX2positive cells in the sensory domain (Oliver et al, 2021).…”
Section: Discussionmentioning
confidence: 95%
“…Consistent with PORCN expression on E14.5, Mybl2 encoded a transcription factor that was also found to be expressed on the medial side of the cochlea, where PORCN enrichment was the highest. MYBL2 is most known for its role in regulating the cell cycle during development and disease (Liu et al, 2022b;Musa et al, 2017;Papetti and Augenlicht, 2011;Ward et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation